Journal with notes by Hugh Gough on India - Gough, Hugh Gough, Viscount, 1779-1869 (1940)
With copies of general orders relating to India together with analysis of the impact of the orders on relationships between the native troops and the government.
Keywords: Gough, Hugh Gough, -- Viscount, -- 1779-1869; East India Company; India -- History -- British occupation, 1765-1947